Pengaruh Pembelajaran Komputer (Microsoft Word) pada Siswa Sekolah Dasar Negeri Jatipasar - Yanda Bara Kusuma; Yahya Kusuma; Ubaidillah Bramantyo Esnanhik; Nindi Aulia Firdiana (Lembaga Pengembangan Kinerja Dosen, 2024)
Abstract: Over time, humans have experienced many adaptations and changes. This underlies and guides everyone to be responsive to every change that exists. Education develops along with the advancement of technology and science in every individual since childhood. To realize all of that, small meaningful steps are needed, such as introducing the world of technology to the younger generation. The goal to be achieved is to familiarize the younger generation with technological developments. This is implemented directly to grade 5 students of SDN Jatipasar. The results of this program are that students are enthusiastic about computer devices. In addition, students' interests and abilities have increased significantly.